Ultrahigh-strength rare earth magnesium alloy deformed material and preparation method thereof

By adding Zn to the magnesium alloy to form the LPSO phase and the partially polymerized pinning technology of Ag and Er at the grain boundary, the problems of poor ductility and low absolute strength of magnesium alloy materials at room temperature are solved, and high strength and high plasticity are achieved Magnesium alloy deformation material has excellent industrial application value.

CN119392073APending Publication Date: 2025-02-07SHANGHAI JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411535125.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Magnesium alloy materials have poor ductility and low absolute strength at room temperature, and the complex deformation process is limited to laboratories, so they have low practical industrial application value.

Method used

The plasticity of the material is significantly improved by adding Zn to form the LPSO phase, and the metaconjugation of Ag and Er at the grain boundary migration, inhibit the growth of grains, adjust the ratio of each metal element in the alloy, and prepare the yield strength Ultra-high strength rare earth magnesium alloy deformation material with tensile strength of 475MPa-488MPa and elongation of 10.8%-11.7%.

Benefits of technology

It has achieved significant improvement in the plasticity and elongation of magnesium alloy without reducing strength, significantly improved the comprehensive mechanical properties of magnesium alloy, and has excellent industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392073A_ABST
    Figure CN119392073A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of rare earth magnesium alloy materials, and discloses an ultrahigh-strength rare earth magnesium alloy deformed material which is prepared from the following raw materials in percentage by mass: 9.5%-10.5% of Gd, 3.0%-4.0% of Y, 1.5%-2.2% of Zn, 0.35%-0.50% of Zr, 0.3%-0.6% of Ag, 0.8%-1.2% of Er and the balance of Mg. The invention further discloses a preparation method of the magnesium alloy deformed material. The preparation method comprises the steps of smelting and casting, homogenizing treatment, variable-speed isothermal extrusion treatment, aging treatment and the like. According to the invention, by adding Ag and Er elements and adjusting the ratio of metal elements in the alloy, the alloy shows excellent comprehensive mechanical properties, the yield strength is 384-390 MPa, the tensile strength is 475-488 MPa, and the ductility is 10.8%-11.7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth magnesium alloy materials, and in particular relates to an ultra-high strength rare earth magnesium alloy deformed material and a preparation method thereof. Background Art

[0002] In order to comply with the development concept of energy conservation and emission reduction, magnesium alloy, as the lightest metal structural material, has been increasingly valued in the fields of aerospace and transportation. However, the two bottleneck problems of poor room temperature ductility and low absolute strength of magnesium alloy have not yet been effectively solved.

[0003] After decades of efforts, the room temperature strength of bulk magnesium alloys has been continuously improved, but it is also accompanied by a decrease in ductility and a continuous reduction in product size. However, the continuous breakthrough in the strength of magnesium alloys is closely related to the complex deformation process of obtaining submicron (0.1-1μm) or nanometer (1-100nm) grain size. However, these complex deformation processes are mostly limited to laboratories. Therefore, these achievements are still largely in the theoretical research stage, and the actual industrial application value is low.

[0004] Chinese patent CN102392166 discloses "a large ingot of Mg-Gd-Y-Zn-Zr alloy and its preparation method". The Mg-Gd-Y-Zn-Zr alloy is a large ingot, which is a large-size ingot made by a semi-continuous casting machine. The patent focuses on the size of the ingot, and also mentions that as the Zn content in the alloy increases, the high-strength rare earth magnesium alloy is prone to cracking, which limits the size of the ingot of ultra-high-strength magnesium alloy, but does not focus on the comprehensive mechanical properties of the ingot, such as mechanical strength and ductility. Summary of the invention

[0005] In order to solve the technical problems of poor ductility and low absolute strength of magnesium alloy materials at room temperature, the present invention provides an ultra-high strength rare earth magnesium alloy deformed material, in which Zn is added to form LPSO phase, which significantly improves the plasticity of the material without reducing the strength; and Ag and Er are segregated at the grain boundaries to strongly pin the grain boundary migration, thereby inhibiting the growth of grains during heat treatment and deformation, thereby effectively improving the performance. At the same time, by adjusting the ratio of each metal element in the alloy, the yield strength of the magnesium alloy deformed material is 384MPa-390MPa, the tensile strength is 475MPa-488MPa, and the elongation is 10.8%-11.7%, showing excellent comprehensive mechanical properties.

[0006] The technical solution of the present invention is as follows:

[0007] The invention provides an ultra-high strength rare earth magnesium alloy deformation material, which is prepared from the following raw materials in mass fraction: Gd 9.5%-10.5%, Y 3.0%-4.0%, Zn 1.5%-2.2%, Zr 0.35%-0.50%, Ag 0.3%-0.6%, Er 0.8%-1.2%, and the balance is Mg.

[0008] The present invention also provides a method for preparing the ultra-high strength rare earth magnesium alloy deformed material, comprising the following steps:

[0009] (1) Melting and casting: weighing the raw materials according to the above mass fractions, melting and casting to obtain magnesium alloy ingots;

[0010] (2) Homogenization treatment: The magnesium alloy ingot is placed at 490-510°C for 18-22 hours, then air-cooled and peeled;

[0011] (3) Variable speed isothermal extrusion treatment: preheating the magnesium alloy ingot after homogenization treatment to 430-440°C, preheating the mold to 390-410°C, maintaining the temperature of the magnesium alloy ingot above 400°C during the extrusion process, and extruding to obtain a rod;

[0012] (4) Aging treatment: The rod is placed at 190-210°C for 30-40 hours, then taken out for air cooling to obtain an ultra-high strength rare earth magnesium alloy deformed material.

[0013] In one embodiment of the present invention, it is also preferred that the raw materials used in step (1) are Mg ingots, Mg-30Gd master alloys, Mg-30Y master alloys, Mg-30Zr master alloys, Mg-30Er master alloys, Zn ingots and Ag ingots.

[0014] In one embodiment of the present invention, it is also preferred that the smelting and casting described in step (1) includes first placing the Mg ingot into the furnace for heating and melting, and passing protective gas, and when the furnace temperature rises to 710-750°C, adding Mg-30Gd intermediate alloy, Mg-30Y intermediate alloy and Zn ingot in sequence, and setting the furnace temperature to 740-750°C after keeping warm for 10 minutes, and continuing to keep warm for 15 minutes, and then adding Mg-30Zr intermediate alloy, Mg-30Er intermediate alloy and Ag ingot in sequence, and continuing to keep warm for 15 minutes for refining, and continuing to stir to obtain alloy liquid, and casting the alloy liquid to obtain magnesium alloy ingot.

[0015] In one embodiment of the present invention, it is also preferred that when the extrusion treatment in step (3) includes extrusion processing, the extrusion ratio is 13-17.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The invention discloses an ultra-high strength rare earth magnesium alloy deformed material. By investigating the intrinsic properties of the magnesium alloy, Zn is added to form an LPSO phase, which significantly improves the plasticity of the material without reducing the strength. In addition, Ag and Er are segregated at the grain boundaries to strongly pin the grain boundary migration, thereby inhibiting the growth of grains during heat treatment and deformation, thereby effectively improving the performance. At the same time, the ratio of each metal element in the Mg-Gd-Y-Zn-Zr alloy is adjusted. The magnesium alloy deformed material exhibits excellent comprehensive mechanical properties, with a yield strength of 384MPa-390MPa, a tensile strength of 475MPa-488MPa, and an elongation of 10.8%-11.7%.

[0018] 1) The maximum solid solubility of Ag in Mg is 15.5wt%, but the saturated solid solubility at 200℃ is close to 0wt%. Therefore, when the Ag-containing alloy is heat treated at 200℃ and below, Ag shows a strong tendency to dissolve. In addition, the radius of Ag atoms is 0.144nm, and the radius of Mg atoms is 0.16nm. The size mismatch between Ag solute atoms and Mg matrix causes lattice distortion, which promotes the precipitation of Ag atoms to segregate at crystal defects (such as dislocations, grain boundaries and other high-energy areas) to reduce strain energy and interface energy. The segregation of Ag atoms at dislocations will hinder the movement of dislocations during recrystallization, resulting in the formation of more dislocation entanglements, thereby providing more nucleation points for recrystallization. The segregation of Ag atoms at grain boundaries will pin grain boundary migration, inhibit grain growth during heat treatment and deformation, and when large-sized RE atoms and small-sized Ag atoms co-segregate at grain boundaries, theoretically, they will have a more significant pinning effect on the grain boundaries. Therefore, adding Ag to rare earth magnesium alloys is beneficial to grain refinement and even induces the formation of ultrafine grains / nanocrystalline.

[0019] 2) The maximum solid solubility of Er in Mg is 32.7wt%, which is much higher than Gd (23.5wt%) and Y (11.4wt%). The saturated solid solubility at 200℃ is still as high as 20wt%. Er is a typical element with no age hardening response, but Er dissolved in the matrix can promote the precipitation of β phase in Mg-Gd alloys. The atomic radius of Er (0.1757nm) is larger than that of Mg (0.1602nm). There is an atomic size mismatch between Er and Mg, which can cause lattice distortion and have a solid solution strengthening effect. Many studies have shown that adding Er to Mg-RE alloys is beneficial to improving strength and plasticity.

[0020] 3) The addition of Zn will form LPSO phase, which increases the critical shear stress of basal slip and activates c+a non-basal slip. The former increases the strength and the latter improves the toughness. Therefore, LPSO has a very important influence on the strength and plasticity of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1A metallographic microstructure photograph of the ultra-high strength rare earth magnesium alloy deformed material of Example 1 of the present invention;

[0022] Figure 2 A metallographic microstructure photograph of the magnesium alloy material of Comparative Example 1 of the present invention;

[0023] Figure 3 A metallographic microstructure photograph of the magnesium alloy material of Comparative Example 2 of the present invention;

[0024] Figure 4 A metallographic microstructure photograph of the magnesium alloy material of Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0026] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0027] An ultra-high strength rare earth magnesium alloy deformed material according to an embodiment of the present invention comprises the following steps:

[0028] (1) Selection of raw materials: The raw materials used for the alloy are Mg ingot, Mg-30Gd master alloy, Mg-30Er master alloy, Mg-30Y master alloy, Mg-30Zr master alloy, Zn ingot and Ag ingot.

[0029] (2) First, the Mg ingot is placed in a furnace for heating and melting, and protective gas is passed through. When the furnace temperature rises to 710-750°C, Mg-30Gd master alloy, Mg-30Y master alloy and Zn ingot are added in sequence, and the temperature is kept at 10 minutes. The furnace temperature is set to 740-750°C and the temperature is kept at 15 minutes. Then, Mg-30Zr master alloy, Mg-30Er master alloy and Ag ingot are added in sequence, and the temperature is kept at 15 minutes for refining and stirring. After the smelting is completed, a molten alloy is obtained; then, the molten alloy is cast into a magnesium alloy billet.

[0030] (3) The magnesium alloy ingot is homogenized by keeping the temperature at 490°C-510°C for 18h-22h, followed by air cooling and peeling. The homogenization process is completed.

[0031] (4) During the variable speed isothermal extrusion process, the magnesium alloy ingot after homogenization treatment is preheated to 430℃-440℃, and the mold is preheated to 390-410℃ to ensure that the temperature is maintained above 400℃ during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 13-17.

[0032] (5) After the isothermal extrusion process is completed, an aging treatment is performed, and the process is as follows: the extruded rod is kept at 190-210°C for 30-40 hours, and then taken out for air cooling.

[0033] The profile variable speed isothermal extrusion technology adopted in the present invention adjusts the extrusion speed in real time based on process simulation, forms a near-isothermal forming environment, and obtains profiles that meet the index performance requirements.

[0034] Example 1

[0035] The method for preparing an ultra-high strength rare earth magnesium alloy deformed material according to embodiment 1 of the present invention comprises the following steps:

[0036] (1) In terms of mass percentage, the raw material content of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment is as follows: Gd: 10.5%, Y: 4.0%, Zn: 2.2%, Zr: 0.5%, Ag: 0.6%, Er: 1.2%, and the balance is Mg.

[0037] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:

[0038] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Er, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Er, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.

[0039] The magnesium alloy ingot was placed in a muffle furnace at 510°C for 20 hours, followed by air cooling, peeling, and homogenization.

[0040] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 440°C, the die is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.

[0041] The extruded rod after isothermal extrusion was kept at 200°C for 36 hours and then taken out for air cooling.

[0042] At room temperature, according to the test requirements of GB-T 228-2002_Room Temperature Tensile Test Method for Metallic Materials, the yield strength of the deformed magnesium alloy was measured by a tensile mechanical properties testing machine to be 384 MPa, the tensile strength was 475 MPa, and the elongation was 11.7%.

[0043] The mechanical property tests of the following Examples 2 to 5 and Comparative Examples 1 to 3 were all carried out in accordance with GB-T228-2002_Room Temperature Tensile Test Method for Metallic Materials.

[0044] Example 2

[0045] The method for preparing an ultra-high strength rare earth magnesium alloy deformed material according to embodiment 2 of the present invention comprises the following steps:

[0046] (1) In terms of mass percentage, the raw material content of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment is as follows: Gd: 9.5%, Y: 3.0%, Zn: 1.5%, Zr: 0.35%, Ag: 0.3%, Er: 0.8%, and the balance is Mg.

[0047] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:

[0048] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Er, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Er, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.

[0049] The magnesium alloy ingot was placed in a muffle furnace at 510°C for 20 hours, followed by air cooling, peeling, and homogenization.

[0050] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 440°C, the die is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.

[0051] The extruded rod after isothermal extrusion was kept at 200°C for 36 hours and then taken out for air cooling.

[0052] At room temperature, the yield strength of the deformed magnesium alloy material was measured by a tensile mechanical properties testing machine to be 390 MPa, the tensile strength was 488 MPa, and the elongation was 10.8%.

[0053] Example 3

[0054] The method for preparing an ultra-high strength rare earth magnesium alloy deformed material according to Embodiment 3 of the present invention comprises the following steps:

[0055] (1) In terms of mass percentage, the raw material content of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment is as follows: Gd: 9.5%, Y: 3.4%, Zn: 2%, Zr: 0.35%, Ag: 0.3%, Er: 1%, and the balance is Mg.

[0056] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:

[0057] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Er, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Er, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.

[0058] The magnesium alloy ingot was placed in a muffle furnace at 510°C for 20 hours, followed by air cooling, peeling, and homogenization.

[0059] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 440°C, the die is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.

[0060] The extruded rod after isothermal extrusion was kept at 200°C for 36 hours and then taken out for air cooling.

[0061] At room temperature, the yield strength of the deformed magnesium alloy material was measured by a tensile mechanical properties testing machine to be 389 MPa, the tensile strength was 488 MPa, and the elongation was 11.4%.

[0062] Example 4

[0063] A method for preparing an ultra-high strength rare earth magnesium alloy deformed material according to embodiment 4 of the present invention comprises the following steps:

[0064] (1) In terms of mass percentage, the raw material content of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment is as follows: Gd: 9.7%, Y: 3%, Zn: 2%, Zr: 0.4%, Ag: 0.5%, Er: 1%, and the balance is Mg.

[0065] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:

[0066] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Er, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Er, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.

[0067] The magnesium alloy ingot was placed in a muffle furnace at 510°C for 20 hours, followed by air cooling, peeling, and homogenization.

[0068] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 440°C, the die is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.

[0069] The extruded rod after isothermal extrusion was kept at 200°C for 36 hours and then taken out for air cooling.

[0070] At room temperature, the yield strength of the deformed magnesium alloy material was measured by a tensile mechanical properties testing machine to be 386 MPa, the tensile strength was 485 MPa, and the elongation was 10.9%.

[0071] Example 5

[0072] A method for preparing an ultra-high strength rare earth magnesium alloy deformed material according to Embodiment 5 of the present invention comprises the following steps:

[0073] 1. In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes: Gd: 10.0%, Y: 3.5%, Zn: 1.8%, Zr: 0.4%, Ag 0.5%, Er 0.8%, and the balance is Mg.

[0074] 2. The preparation method of the ultra-high strength rare earth magnesium alloy deformed material of this comparative example includes the following steps:

[0075] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, and Mg-30Zr. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then add Mg-30Zr alloying elements, and continue to keep warm for 15min. Then refine and stir, and the refining agent takes 1.2% of the total batch weight, that is, 0.06kg. Take a small ingot from the melt and measure the direct reading spectrum. If the composition meets the standard, let the melt stand for 45 minutes before casting. If the composition does not meet the standard, add material until the final direct reading composition is close to the nominal composition.

[0076] The magnesium alloy ingot was placed in a muffle furnace at 510°C for 20 hours, followed by air cooling, peeling, and homogenization.

[0077] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 440°C, the die is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.

[0078] The extruded rod after isothermal extrusion was kept at 200°C for 36 hours and then taken out for air cooling.

[0079] At room temperature, the yield strength of the deformed magnesium alloy material was measured by a tensile mechanical properties testing machine to be 384 MPa, the tensile strength was 485 MPa, and the elongation was 11.4%.

[0080] Comparative Example 1:

[0081] The preparation method of the magnesium alloy material of Comparative Example 1 comprises the following steps:

[0082] 1. In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes:

[0083] Gd: 10.0%, Y: 3.5%, Zn: 1.8%, Zr: 0.4%, and the balance is Mg.

[0084] 2. The preparation method of the magnesium alloy deformed material of this comparative example includes the following steps:

[0085] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, and Mg-30Zr. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then add Mg-30Zr alloying elements, and continue to keep warm for 15min. Then refine and stir, and the refining agent takes 1.2% of the total batch weight, that is, 0.06kg. Take a small ingot from the melt and measure the direct reading spectrum. If the composition meets the standard, let the melt stand for 45 minutes before casting. If the composition does not meet the standard, add material until the final direct reading composition is close to the nominal composition.

[0086] The magnesium alloy ingot was placed in a muffle furnace at 510°C for 20 hours, followed by air cooling, peeling, and homogenization.

[0087] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 440°C, the die is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.

[0088] The extruded rod after isothermal extrusion was kept at 200°C for 36 hours and then taken out for air cooling.

[0089] At room temperature, the yield strength of the deformed magnesium alloy material was measured by a tensile mechanical properties testing machine to be 354 MPa, the tensile strength was 442 MPa, and the elongation was 8.6%.

[0090] Comparative Example 2

[0091] The preparation method of the magnesium alloy material of Comparative Example 2 comprises the following steps:

[0092] 1. In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes:

[0093] Gd: 10.0%, Y: 3.5%, Zn: 1.8%, Zr: 0.4%, Er: 0.8%, and the balance is Mg.

[0094] 2. The preparation method of the ultra-high strength rare earth magnesium alloy deformed material of this comparative example includes the following steps:

[0095] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, and Mg-30Er. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr and Mg-30Er alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.

[0096] The magnesium alloy ingot was placed in a muffle furnace at 510°C for 20 hours, followed by air cooling, peeling, and homogenization.

[0097] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 440°C, the die is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.

[0098] The extruded rod after isothermal extrusion was kept at 200°C for 36 hours and then taken out for air cooling.

[0099] At room temperature, the yield strength of the deformed magnesium alloy material was measured by a tensile mechanical properties testing machine to be 360 ​​MPa, the tensile strength was 448 MPa, and the elongation was 10.7%.

[0100] Comparative Example 3

[0101] The preparation method of the magnesium alloy material of Comparative Example 3 comprises the following steps:

[0102] 1. In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes:

[0103] Gd: 10.0%, Y: 3.5%, Zr: 0.4%, and the balance is Mg.

[0104] 2. The preparation method of the ultra-high strength rare earth magnesium alloy deformed material of this comparative example includes the following steps:

[0105] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, and Mg-30Zr. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd and Mg-30Y. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then add Mg-30Zr alloying elements, and continue to keep warm for 15min. Then refine and stir, and the refining agent takes 1.2% of the total batch weight, that is, 0.06kg. Take a small ingot from the melt and measure the direct reading spectrum. If the composition meets the standard, let the melt stand for 45 minutes before casting. If the composition does not meet the standard, add material until the final direct reading composition is close to the nominal composition.

[0106] The magnesium alloy ingot was placed in a muffle furnace at 510°C for 20 hours, followed by air cooling, peeling, and homogenization.

[0107] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 440°C, the die is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.

[0108] The extruded rod after isothermal extrusion was kept at 200°C for 36 hours and then taken out for air cooling.

[0109] At room temperature, the yield strength of the magnesium alloy deformed material was measured by a tensile mechanical properties testing machine to be 330 MPa, the tensile strength was 394 MPa, and the elongation was 6.4%.

[0110] The component contents of Examples 1 to 5 are all within the scope of the component contents of the present invention, wherein, Comparative Example 1 does not add Ag and Er elements, Comparative Example 2 does not add Ag elements, and Comparative Example 3 does not add Zn, Ag and Er elements, and the others are the same as Example 5. As shown in Table 1, it can be seen from the room temperature tensile mechanical property test results that the comprehensive mechanical properties of Examples 1 to 5 are significantly higher than those of Comparative Examples 1 to 3. In the field of magnesium alloy materials, it is difficult to increase the absolute mechanical strength after reaching a limit value. The tensile strength of the present invention is increased by nearly 30MPa, the yield strength is increased by nearly 30MPa, and the elongation is maintained at 10.8%-11.7%. The magnesium alloy deformed material of the present invention exhibits excellent comprehensive mechanical properties, with a yield strength of 384MPa-390MPa, a tensile strength of 475MPa-488MPa, and an elongation of 10.8%-11.7%.

[0111] From the metallographic microstructure, it can be seen that the grain size of the alloy in Example 1 of the present invention is significantly smaller than that in Comparative Examples 1 to 3, and compared with Comparative Examples 1 and 2, the bulk LPSO is less, and the alloy in Comparative Example 3 does not contain LPSO phase. Figures 1 to 4 shown. The present invention adds Zn to form LPSO phase, which significantly improves the plasticity of the material without reducing the strength; and, by Ag and Er in the crystal The segregation at the boundary strongly pins the grain boundary migration, inhibiting the grain growth during heat treatment and deformation, thereby achieving effective performance promote.

[0112] Table 1 Room temperature mechanical properties of the embodiments and comparative examples

[0113] Serial number Tensile strength(MPa) Yield strength(MPa) Elongation(%) Example 1 475 384 11.7 Example 2 488 390 10.8 Example 3 488 389 11.4 Example 4 485 386 10.9 Example 5 485 384 11.4 Comparative Example 1 442 354 8.6 Comparative Example 2 448 360 10.7 Comparative Example 3 394 330 6.4

[0114] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An ultra-high strength rare earth magnesium alloy deformed material, characterized in that: Made from the following raw materials by mass fraction: Gd 9.5%-10.5%, Y 3.0%-4.0%, Zn 1.5%-2.2%, Zr 0.35%-0.50%, Ag0.3%-0.6%, Er 0.8%-1.2%, and the balance is Mg.

2. A method for preparing the ultra-high strength rare earth magnesium alloy deformed material according to claim 1, characterized in that: The following steps are involved: (1) Melting and casting: weighing raw materials according to the mass fraction of claim 1, melting and casting to obtain a magnesium alloy ingot; (2) Homogenization treatment: The magnesium alloy ingot is placed at 490-510°C for 18-22 hours, then air-cooled and peeled; (3) Variable speed isothermal extrusion treatment: preheating the magnesium alloy ingot after homogenization treatment to 430-440°C, preheating the mold to 390-410°C, maintaining the temperature of the magnesium alloy ingot above 400°C during the extrusion process, and extruding to obtain a rod; (4) Aging treatment: The rod is placed at 190-210°C for 30-40 hours, then taken out for air cooling to obtain an ultra-high strength rare earth magnesium alloy deformed material.

3. The method for preparing the ultra-high strength rare earth magnesium alloy deformed material according to claim 2, characterized in that: The raw materials used in step (1) are Mg ingots, Mg-30Gd master alloys, Mg-30Y master alloys, Mg-30Zr master alloys, Mg-30Er master alloys, Zn ingots and Ag ingots.

4. The method for preparing the ultra-high strength rare earth magnesium alloy deformed material according to claim 3, characterized in that: The smelting and casting described in step (1) include first placing the Mg ingot into a furnace for heating and melting, and passing a protective gas, and when the furnace temperature rises to 710-750°C, adding Mg-30Gd master alloy, Mg-30Y master alloy and Zn ingot in sequence, and setting the furnace temperature to 740-750°C after keeping warm for 10 minutes, and continuing to keep warm for 15 minutes, and then adding Mg-30Zr master alloy, Mg-30Er master alloy and Ag ingot in sequence, and continuing to keep warm for 15 minutes for refining, and continuing to stir to obtain alloy liquid, and casting the alloy liquid to obtain a magnesium alloy ingot.

5. The method for preparing the ultra-high strength rare earth magnesium alloy deformed material according to claim 2, characterized in that: The extrusion treatment in step (3) includes an extrusion process in which the extrusion ratio is 13-17.

Citation Information

Patent Citations

  • Magnetic head cleaning cassette

    GB2282002A